2021
DOI: 10.4103/aer.aer_59_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intrathecal Fentanyl and Buprenorphine as an Adjuvant to 0.5% Hyperbaric Bupivacaine for Spinal Anesthesia

Abstract: Purpose: This study was designed to evaluate and compare three groups, that is, (1) normal saline 0.5 mL with 15 mg of 0.5% hyperbaric bupivacaine normal (BN), (2) intrathecal fentanyl 25 μg (0.5 mL) as an adjuvant to 15 mg of 0.5% hyperbaric bupivacaine fentanyl (BF), and (3), 150 μg buprenorphine with 15 mg of 0.5% hyperbaric bupivacaine buprenorphine (BB) with respect to the onset and duration of sensory and motor spinal block, level of anesthesia, effects on hemodynamic parameters, requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…En los tres grupos, la hipotensión se presentó en más del 50%, observándose que en el grupo BM fue, en la mayoría de los casos, antes de la entrada de compresas a cavidad, y en los grupos BBMD y FBMD posterior a ésta. (3,4) , y que el manejo anestésico con buprenorfina como coadyuvante a otros anestésicos espinales prolongan la duración de la misma con menos bloqueo motor y mayor analgesia postoperatoria (9)(10)(11)(12) . Por su alta liposolubilidad, la buprenorfina tiene mayor afinidad por la sustancia blanca, la grasa peridural y la mielina, y de ahí es aclarada al plasma con rapidez, llegando a los receptores opiáceos sólo un 8% (5) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…En los tres grupos, la hipotensión se presentó en más del 50%, observándose que en el grupo BM fue, en la mayoría de los casos, antes de la entrada de compresas a cavidad, y en los grupos BBMD y FBMD posterior a ésta. (3,4) , y que el manejo anestésico con buprenorfina como coadyuvante a otros anestésicos espinales prolongan la duración de la misma con menos bloqueo motor y mayor analgesia postoperatoria (9)(10)(11)(12) . Por su alta liposolubilidad, la buprenorfina tiene mayor afinidad por la sustancia blanca, la grasa peridural y la mielina, y de ahí es aclarada al plasma con rapidez, llegando a los receptores opiáceos sólo un 8% (5) .…”
Section: Resultsunclassified
“…La falta de conocimiento sobre su seguridad, farmacocinética y farmacodinamia, así como, una interpretación incorrecta de los términos «actividad intrínseca», «eficacia» y agonista «total o parcial» ha hecho que muchos médicos pasen por alto su uso; además, la buprenorfina presenta un efecto techo para la depresión respiratoria, pero no para la analgesia (8) . Su alta liposolubilidad, gran afinidad por los receptores mu y su acción prolongada han hecho de la buprenorfina un adyuvante excelente para los anestésicos locales en la anestesia espinal, ya que prolonga la duración de la misma, con menos bloqueo motor y mayor analgesia postoperatoria (9)(10)(11)(12) . El objetivo de este estudio fue sustituir al fentanilo por buprenorfina en la AMI para evaluar si, al combinarla con los demás medicamentos, tiene eficacia anestésica en las HTA.…”
Section: Abstract: Multimodal Anesthesia Buprenorphine Fentanyl Hyper...unclassified
“…Shrinivas et al 13 also observed a lower incidence of nausea and vomiting with buprenorphine, which aligns with our results. Dhawale et al 17 investigated the use of intrathecal fentanyl instead of buprenorphine and reported similar outcomes in terms of analgesic duration. However, no studies directly comparing bupivacaine-buprenorphine combination with bupivacaine alone for cesarean delivery were found.…”
Section: Discussionmentioning
confidence: 96%